(untitled) (Research, Society and Development, 2021)
The objective of the research was to analyze professional training in the field of gerontology, through scientific productions for the recognition of teaching strategies used in geriatric nursing education, both for the quality of care provided by nurses in relation to the family and that of family caregivers. The method used was the Integrative Review of Qualitative Literature held from July to August 2020. Through the combination of Boolean operators "and" and "or", fifty scientific productions were identified, however, eight met the requirements of the study in view of the inclusion/exclusion criteria. In the teaching of gerontology, the training of nursing students must be strengthened by methods and learning strategies aimed at developing a set of skills for care. However, nursing education is related to the extension of significant results of professional training, the process of caring for the elderly and the quality of family care.